Translation and Interpreting students enrolled in Taller General Inglés I course during the 2020-II - Villanelo Ninapaytan, María (2021)
The research was focused on Translation and Interpreting students enrolled in Taller General Inglés I  course during the 2020-II semester at the Faculty of Humanities of a Private University in Lima, who are beginning to have their first contact with the translation practice. Therefore, it is common for students to make mistakes in their translations at this stage. However, beyond penalizing errors and seeing them as negative aspects, Hurtado (2001) considers that errors in translation should be used as a key tool for students' learning, so that they themselves develop a critical and analytical sense in their translations as part of their teaching and learning process. Our main objective was to identify the types of errors made by students of Taller General Inglés I, specifically those errors that affect comprehension and expression. For this purpose, we selected a sample of 23 students who were asked to translate a general text. Significant percentages were evidenced in terms of errors affecting comprehension and expression, being errors of expression greater than those of comprehension.